Evidence-Based Medicine Training in United States–Based Physiatry Residency Programs. (8th July 2022) - Annaswamy, Thiru M.; Rizzo, John-Ross; Schnappinger, Amy; Morgenroth, David C.; Engkasan, Julia Patrick; Ilieva, Elena; Arnold, W. David; Boninger, Michael L.; Bean, Allison C.; Cirstea, Carmen M.; Dicianno, Brad E.; Fredericson, Michael; et al.
Abstract: Although the physiatric community increasingly embraces evidence-based medicine (EBM), the current state of EBM training for trainees in physiatry is unclear. The purposes of this article are to report the results of the Association of Academic Physiatrists' surveys of physiatry residency programs in the United States, to discuss the implications of their findings, and to better delineate the "baseline" upon which sound and clear recommendations for systematic EBM training can be made. The two Association of Academic Physiatrists surveys of US physiatry residency programs reveal that most survey respondents report that they include EBM training in their programs that covers the five recommended steps of EBM core competencies. However, although most respondents reported using traditional pedagogic methods of training such as journal club, very few reported that their EBM training used a structured and systematic approach. Future work is needed to support and facilitate physiatry residency programs interested in adopting structured EBM training curricula that include recommended EBM core competencies and the evaluation of their impact.